Pengaruh Lingkungan Tempat Tinggal, Motivasi Belajar, dan Sikap Siswa Terhadap Prestasi Belajar Matematika Siswa - Nely Indra Meifiani (Jurnal Penelitian Pendidikan, 2013)
This was a quantitative study which was ex post facto in nature. The datacollecting instruments consisted of a questionnaire and a mathematics learningachievement test. The results of the study show that: 1) there are not effects ofneighborhoods, learning motivation, and students’ attitudes towards Mathematics as anaggregate on Mathematics learning achievements; 2) there are not relationship betweenneighborhoods and JHS students’ Mathematics learning achievements; 3) there arerelationship between learning motivation and JHS students’ Mathematics learningachievements; and 4) there are not relationship between students’ attitudes towardsMathematics and JHS students’ Mathematics learning achievements.